Internal Auditors’ Independence and Financial Performance of Listed Banks at the Nairobi Securities Exchange - Mburunga, Elicana Mwiti; Walubuka, Dr. Elijah; Gichana, Mr. Ignatius (International Journal of Scientific Research and Management (IJSRM), 2019)
The internal audit function plays a significant role in the financial performance of banks as it tasked with not only carrying out an oversight function but also providing assurance to their stakeholders. It is also required of an internal auditor to undertake assessment on the status of internal controls as well provide recommendations on the same albeit independently. However, these functions are adversely influenced by interference from top management leading to a significant negative impact on the financial performance of banks. Specifically this research based its investigation on the influence of internal auditors’ independence on financial performance of listed banks at the Nairobi Securities Exchange (NSE). The study is pivoted on two theories; Agency Theory and Market Power Theory. This research was guided by Descriptive survey research design. The study’s target population constituted of 76 Audit Managers and Internal auditors. A sample size of 76 final sampled subjects was used and respondents selected using Census sampling technique.  A questionnaire was prepared and used for primary data collection from the target final sampled subjects. Descriptive statistics was employed in the analysis of quantitative data while narratives guided by themes under research were employed in the reporting of qualitative data. A Chi Sqaure was employed to test hypothesis. The research established that limited or minimal internal auditors’ independence negatively influenced financial performance of listed banks at the NSE. In particular, the study established that the existence of an internal audit budget as a measure of improving internal auditors’ independence influenced the financial performance of commercial banks listed in NSE. Additionally, this research established that recognized the need to enhance of Internal audit as a training ground for managers meaning most of the study’s final subjects appreciated the need to gain experience prior to been promoted to an audit manager position for excellent work performance. The scholarly investigation concluded that internal audit budget that determines internal auditors’ independence has a significant influence on the financial performance of listed banks. The research recommends that as a measure of enhancing internal auditor independence, commercial dependable banks listed at the Nairobi Securities Exchange (NSE) should invest financial resources in the form of a budget to their internal audit departments.